The pricing of sustainable syndicated loans - Alves, Paulo (2023)
This paper provides a comparative analysis of sustainable and conventional syndicated loan spreads and pricing. Using a cross-section of 24,962 syndicated loan tranches closed between 2018 and 2022 in OECD countries, we show that sustainable and conventional loans are differently priced, spreads of sustainable versus conventional loans do not differ significantly, and banks rely on contractual, macroeconomic, bank syndicate structure, and borrowers’ characteristics when pricing sustainable tranches. At the deal-level, our results do not support the hypothesis of sustainable debt financing as a mechanism for reducing firms’ funding costs. We also find that economies of scale, institutional, and information asymmetry arguments affect firms’ choice between sustainable and conventional syndicated deals.